Social capital and gender in South Africa, 1993-98 - Maluccio, John A.; Haddad, Lawrence J.; May, Julian (International Food Policy Research Institute, 2003)
The concept of social capital, well grounded in the sociological and anthropological literatures (for example, Coleman 1988), is increasingly being analyzed and used by economists and other development policy practitioners. The entry point for many economists is Robert Putnam’s research on Italian regional economic performance (Putnam 1993) and his subsequent work in the United States. For Putnam, “social capital refers to features of social organization such as networks, norms, and social trust that facilitate coordination and cooperation for mutual benefit” (Putnam 1995, 67). This research adds a gender dimension to the debate providing empirical evidence on the role of social capital. The goal of the research is to determine whether men and women have social capital to the same degree and whether men’s and women’s social capital, proxied by membership in formal and informal groups, had differential effects on household welfare in South Africa in the 1990s.